Effect of basalt fibers dispersion on steel fire protection performance of epoxy-based intumescent coatings - Yasir, M. (Elsevier B.V., 2018)
Epoxy-based intumescent coatings are widely used in oil and gas industries, shopping complexes and petrochemical plants to provide fire protection to the metallic substrates during the event of a fire. The present work shows how the incorporation of basalt fibers as filler material in an epoxy-based intumescent coating enhances its thermal insulation property. Dispersing agents (ethanol or glycidyl ether) were also added to the coating and their effects on the dispersion of the basalt fibers and the thermal performance of the coating were also discussed. Bunsen burner (ASTM E119) and expansion tests were performed to study the influence of basalt fibersâ dispersion on the thermal insulation property of the coating. Coatings and their chars were also analysed by Field Emission Electron Microscopy (FESEM), Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD) and X-Ray Photoelectron Spectroscopy (XPS) analyses. Thermal stability was investigated using Thermogravimetric Analysis (TGA) in the pyrolysis conditions. Fire test results showed that the formulation containing ethanol as dispersing agent provided a higher fire protection, whereby the backside of the steel plate can reach a very stable plateau at 189 Â°C after 15 min exposure. It is also shown that the coating reached the highest expansion of 1087 with a very homogeneous char structure. The FESEM images also confirmed that basalt fibers were well dispersed when ethanol was used, whereas aggregates were formed when no dispersing agent was added. XRD and FTIR showed that the presence of boron oxide, boron phosphate, carbon and silica in the formulations which are thermally stable can improve the thermal performance of the intumescent coating. Finally, TGA confirmed that the thermal stability of formulations containing dispersing agents has been improved. Â© 2018